2004
DOI: 10.1046/j.0767-3981.2003.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine‐induced severe pulmonary toxicity

Abstract: Gemcitabine is a relatively new deoxycytidine analog (2',2'-difluorodeoxycytidine) with structural similarities to cytosine arabinoside (Ara-C). Activity of gemcitabine is demonstrated in the treatment of many solid tumors, like pancreas, ovarian and nonsmall cell lung cancer (NSCLC). Although gemcitabine is considered as a drug with a good safety profile, cases of gemcitabine-induced severe pulmonary toxicity (GISPT) were reported as for Ara-C. We performed a systematic review of reported cases on the GISPT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 51 publications
4
87
2
2
Order By: Relevance
“…It is unclear whether alkaline phosphatase is related to lung toxicity or is a coincidental effect of gemcitabine, though they seemed to occur simultaneously in this patient. In a recent review, the onset of toxicity occurred at a median of the second cycle, though it also occurred after the first administration or several cycles thereafter [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear whether alkaline phosphatase is related to lung toxicity or is a coincidental effect of gemcitabine, though they seemed to occur simultaneously in this patient. In a recent review, the onset of toxicity occurred at a median of the second cycle, though it also occurred after the first administration or several cycles thereafter [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few reports have described gemcitabine-induced lung toxicity [1][2][3][4][5][6][7]. Recently, this toxicity was reported in patients with ovarian cancer [2,8,9]. Although up to 23% of patients treated with gemcitabine may develop dyspnea, a small fraction of patients may develop severe dyspnea, diffuse alveolar damage, acute respiratory distress syndrome, interstitial pneumonitis, or noncardiogenic pulmonary edema requiring steroid therapy [2, 4, 5, 8 -10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] To avoid severe toxicity and improve survival, GMT-based therapy is often used in combination with other agents. 6,[20][21][22][23][24][25][33][34][35][36] We have previously shown that TMX, as a CaM antagonist, induces apoptosis in human cholangiocarcinoma cells, which lack ERs. [10][11][12][13] We reported that TMX-induced apoptosis is partially dependent on inhibition of pAKT and FLIP expression, as well as activation of caspases 8, 10, 9, and 3.…”
Section: Discussionmentioning
confidence: 99%
“…32 Low dose of GMT is preferred to avoid severe toxicity, especially pulmonary toxicity. [33][34][35][36] Hence, combination therapies with GMT plus a variety of chemotherapeutic agents have been employed to minimize toxicity and maximize therapeutic efficacy. Currently, GMT combined with chemicals like leucovorin, 5-fluorouracil, capecitabine, and platinum agents have shown enhanced therapeutic effects in cholangiocarcinoma.…”
mentioning
confidence: 99%